From questionnaire to practical application: A quality of life profile for populations with diverse disabilities. Issue 3 (May 2022) - Jespersen, Louise N; Andersen, Anette; Due, Pernille; Ersbøll, Annette K; Damsgaard, Mogens T; Michelsen, Susan I
Aims: Existing quality of life questionnaires are either disease specific or generic in their assessment of themes which are perceived important to the quality of life in populations with disabilities. To be able to improve quality of life in a population with diverse disabilities there was a need for a cross-disability instrument. The Electronic Quality of Life (EQOL)-questionnaire was developed to meet this need. It is crucial that such an instrument is validated, easy to use, and interpret by, for example, clinicians and policy planners. This study aims to test the content validity of the EQOL questionnaire and to construct a user-friendly, cross-disability quality of life profile. Methods: To further test the content validity of the EQOL-questionnaire, we conducted field test analyses on 318 individuals (aged 16–64) with self-reported disabilities. Comments on the questionnaire were scrutinised and sorted. A profile with six domains of quality of life was developed. Model fit was evaluated by confirmatory factor analysis and content validity was evaluated based on distributions. Results: The EQOL-questionnaire was found to have an acceptable content validity and respondents from the field test found that it features important themes of quality of life. The confirmatory factor analysis estimated a satisfying model fit by the root-mean-squared error of approximation (0.06), whereas the comparative fit index and goodness of fit index indicated poorer model fit. Graphical charts, with colour categories for user-friendly interpretation, were constructed. Conclusion: By identifying themes reported as problematic, the EQOL-profile can be used to inform and target interventions aiming to improve quality of life in populations with diverse disabilities.